2016
DOI: 10.1007/s11764-016-0524-9
|View full text |Cite|
|
Sign up to set email alerts
|

A comparison of heterosexual and LGBTQ cancer survivors’ outlooks on relationships, family building, possible infertility, and patient-doctor fertility risk communication

Abstract: LGBTQ cancer survivors may display more adaptive coping with respect to relationships and fertility loss. Oncology professionals may want to proactively introduce positive coping strategies to reduce distress among AYA cancer survivors at risk for infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…The search returned 518 unique articles that were screened by title and abstract (Figure ). Eighteen papers were screened in full, with 2 studies excluded for not including qualitative data and 1 study excluded for not addressing the phenomenon of interest . Fifteen articles were critically appraised, and all were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The search returned 518 unique articles that were screened by title and abstract (Figure ). Eighteen papers were screened in full, with 2 studies excluded for not including qualitative data and 1 study excluded for not addressing the phenomenon of interest . Fifteen articles were critically appraised, and all were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that listed sources of funding, the most commonly cited sources were the National Institutes of Health (n = 5), the American Cancer Society (n = 3), and the Susan G. Komen Foundation (n = 4). In total, 7 studies reported on GM status: 5 studies collected GM status and combined those individuals with SMs, 1 additional study included GMs as a distinct group, and 1 study focused on transgender and gender‐nonconforming patients …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, no lesbian, gay, bisexual, transgender, or queer (LGBTQ) survivors were interviewed. Interestingly, LGBTQ survivors seem more open toward alternatives to biological parenthood and may be less emotionally affected by infertility . Overall, quantitative research is needed to assess the magnitude of issues identified in this study and allow for identifying vulnerable (sub‐)groups.…”
Section: Study Limitationsmentioning
confidence: 99%